The patterns of phalangeal fractures in children and adolescents: a review of 512 cases - Kralj, Rok; Barcot, Zoran; Vlahovic, Tomislav; Kurtanjek, Mario; Petracic, Ivan (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2019)
Introduction Fractures of the phalanges in children can often be underappreciated by the physician of first contact. Therefore it is necessary to point out which of these fractures, because of the risk of possible future complications, need special mention.Materials and Methods A retrospective review of 512 fractures of the phalanges in children and adolescents during an one year period. Fractures were subdivided into the following categories – physeal fractures, intraarticular (phalangeal neck and condylar) fractures, shaft fractures, tuft fractures, “mallet finger” fractures, volar plate avulsion injuries and collateral ligament avulsion injuries. Main outcome measures was the necessity for operation while the average age at which the injury has occured, the cause of the injury, the frequency of injury of each finger, the necessity for reduction, and the duration of splinting were the secondary outcome measures.Results Collateral ligament avulsion injuries and intraarticular (phalangeal neck and condylar) fractures were injuries which most often necessitated operative treatment. Physeal injuries were the most common injuires with avulsions of the volar plate being the second most common. Accidents during sport was by far the most common cause of injuires in all categories apart from tuft injuries.Conclusion The findings regarding the incidence and the cause of these injuries in this study support the already published dana in the literature. The physician of first contact has to be capable to recognise the problematic fractures – intraarticular (phalangeal neck and condylar), significantly displaced Salter-Harris type III and IV fractures and collateral ligament avulsion injuries and Seymour fractures.
Keywords: Phalanx fractures; children; adolescence